Balancing Social Welfare and Environmental Conservation: A Sustainable Tourism Model in Wonosobo - Fajri, Afrizal; Ikawati, Erina; Hidayat, Muhammad Chanif; Prakoso, Septyanto Galan; Yamin, Muhammad (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
Abstract. This study investigates how Wonosobo Regency—a region known for its cultural heritage and natural landscapes—navigates the complex interplay between economic development, environmental sustainability, and cultural preservation. It examines the role of the Knowledge-Based Economy (KBE) as a key enabler of glocalization, allowing the region to adopt global best practices while maintaining local identity. Through literature review and policy analysis, the study finds that KBE enhances sustainable tourism governance by fostering local knowledge production, innovation, and stakeholder collaboration. The application of ICT, human capital development, and data-driven policies contributes to more effective tourism management and cultural safeguarding. Moreover, circular economy principles and community-based tourism initiatives help balance growth and conservation. The findings suggest that integrating KBE strengthens Wonosobo’s global competitiveness without eroding its cultural uniqueness, offering valuable insights for policymakers and practitioners aiming to promote glocalization in culturally and ecologically significant regions.